Lexical complexity, interactive competence and participation style of ESL learners in face-to-face and online discussions / Chew Shin Yi - Chew, Shin Yi (2013)
To gain a better understanding of the potential of synchronous online discussions, this study compared the ESL learners’ participation styles and discourse which displayed lexical complexity and interactive competence in online and face-to-face discussions. The influence of the learners’ personality and language proficiency in different discussion settings was also investigated. The Ecological Model of the Communication Process (Foulger, 2004) was used as a theoretical framework in this study. The type of personality focused on in this study was the extroversion and introversion of the learners while the language proficiency of the participants of this study was either high-intermediate or low-intermediate. The mixed-method approach used in this study employed the concurrent transformative design in which quantitative and qualitative data were gathered from the stage of data collection to data analysis. This measure can triangulate the data and give better support for the findings. In this study, the quantitative method was utilised to collect and analyse the data gathered from the quasi-experiment and the survey carried out after that. Meanwhile, the qualitative method was used in the collection and analysis of the online feedback session, the learners’ comments in the survey and their responses during the experiment (based on the transcripts and researcher’s observation). Eight sessions of face-to-face and online discussions have been carried out weekly for over a month with two matched-samples groups alternating weekly from online to face-to-face settings. Each group consisted of 24 sixteen-year-old Form 4 ESL students from a secondary school in Kuala Lumpur. This study found that the use of a synchronous online setting can be very helpful in balancing the participation of the learners and eliciting more contribution of words; especially among the introverts and the less proficient ESL learners. The less proficient iv learners have also shown better interactive competence in online discussions. The empirical evidence from this experimental study showed that the online environment can be a good alternative platform for discussions to be held. Following Foulger’s (2004) Ecological Model of the Communication Process and the SLA theories, the communication process in discussions can be made more effective in the synchronous online medium as the learners’ affective filter became lower and they felt more confident and motivated to engage themselves with the interactive language practice. From the findings of this study, a model which described the communication process among the ESL learners in face-to-face and online environment was drawn and named The Group Discussion Model for ESL Learners. Suggestions for facilitating discussion activities in an ESL classroom were also provided. All in all, the use of technology in an ESL classroom should be promoted. More importantly, the learners’ personalities and language proficiency should be considered when choosing the discussion setting and facilitating the discussion activities.